Collaborative Governance In Managing Educative Tourism Of Jogja Exotarium In Sleman Regency 2019 - Hakim, Arif Rahman; Zaenuri, Muchamad; Fridayani, Helen Dian (Journal of Governance and Public Policy, 2019)
The involvement of three pillars in tourism management, namely the government, society and the private sector is very important, this is called collaborative governance. Recently the center of attention is the exotarium or mini zoo Jogja. Jogja Exotarioum or mini zoo and education center is an educational tourism park that displays knowledge about animals. Jogja exotarium offers a variety of animal rides equipped with various facilities, such as children's swimming pools, fishing ponds, children's tubing, fisheries education, livestock education, agricultural education, outbound training to café and restaurant and spot selfi for visitors. The method used in this study is a qualitative method in which one of the research procedures that produces descriptive data in the form of speech or writing and the behavior of the people observed. Data collection techniques carried out are by way of in-depth interviews with each of the stakeholders, namely the government, the private sector and the community. Besides this, it is also supported by secondary data such as regulations, journals, books, and others. The results of this study indicate that the role of each stakeholder in the management of Jogja Exotarium education tours in Sleman Regency is the government as a control over education tourism management, the community as employees, and the private sector as the tourism manager. The process of collaborative governance in the management of educational tourism with 5 indicators used to measure collaborative governance is good, but the collaborative level carried out is still the beginning, which means harming the government, because the government has not been able to interfere too far in managing the tourism. Even if you have shared the risk and there is government involvement in implementation, it will benefit the government.